THE WOMB RENTAL CONTRACT BETWEEN THE LEGITIMATE AND THE LAW - Dr. Sanaa Khudhair Mohammed al-Jaberi; Dr. Ismaiel Ogla Abdullateef; Dr . Jumaah Hussein Ali (Scholars Digest Publishing, 2025)
There is a rule used by Western countries, which is that the end justifies the means, in order to justify their transgressions ensuing from the interaction of modern biological and medical technologies and sciences with their abnormal cultures. They considered childbirth through surrogate mothers as a means to achieve the goal of motherhood without taking into account the religious, moral, and legal aspects. It did not stop there, but rather went beyond that and broke into Arab and Islamic countries alike, which made researchers address this issue to ensure its legal ruling, because of the effects and dimensions of this phenomenon on religious and moral principles and values. Because of the harm to the wife’s womb and the desire of the spouses to have children, they agree with a woman who agrees to rent her womb to them in exchange for Money under a contract called (the womb rental contract), which is a new type of contract that has shown many legal problems since its appearance in Western countries until it has spread throughout the world. What concerns us as Muslims is the issue of the purity of genealogy, the restriction of sexual relations, and what is related to wombs in the circle of legitimate marriage.
Keywords: Contract - The womb rental - Sharia – Law.